Furyborn: Empirium Series #1 - Legrand, Claire, 1986- (Naperville, Illinois : Sourcebooks Fire, 2018)
Rielle may prove to be one of the Prophesized Queens, if she survives the trials, and a thousand years later bounty hunter Eliana helps a girl who could be the answer to the prophecy.
Keywords: Fantasy